2014
DOI: 10.3389/fphar.2014.00198
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery of cochlear fibrocytes after severe degeneration caused by acute energy failure

Abstract: Cochlear fibrocytes in the lateral wall region play a critical role in the regulation of inner ear ion and fluid homeostasis, although these are non-sensory cells. Along with other non-sensory cells, fibrocytes in the spiral ligament have been reported to repopulate themselves after damage. However, the studies of regeneration of cochlear fibrocytes have been difficult because a suitable fibrocyte-specific degeneration model did not exist. Therefore, we analyzed cochlear fibrocytes using a rat model of acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Immunohistochemistry revealed that these cells were SLFs and the examination at different time points revealed that the number of those cells declined as the mice aged. Since slow-cycling cells in general contain a stem/progenitor cell population, manipulating those fibrocytes may accelerate repopulation, leading to the development of promising therapeutic strategies for treating some types of sensorineural hearing loss, such as presbyacusis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry revealed that these cells were SLFs and the examination at different time points revealed that the number of those cells declined as the mice aged. Since slow-cycling cells in general contain a stem/progenitor cell population, manipulating those fibrocytes may accelerate repopulation, leading to the development of promising therapeutic strategies for treating some types of sensorineural hearing loss, such as presbyacusis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of SSNHL cases still remain idiopathic. 7,49 Several hypotheses about the pathophysiology of idiopathic SSNHL have already been proposed; 5063 the most widely accepted theories are direct vascular damage, 40–50 cochlear membrane rupture, 51,52 auto-immunity or immune-mediated disorder, 5257 viral infection, 4,5863 and stress response theory. 59 However, at least in some cases, an etiologic agent (either vascular, infective, or immune-mediated) could damage hair cells, indirectly, disrupting their metabolic activity, reversibly or irreversibly.…”
Section: Resultsmentioning
confidence: 99%
“…the stria vasularis or spiral ligament fibrocytes) and consequentially causing sudden loss of hearing (partial or total); or (2) the possibility of hearing recovery (partial or total) due to the spontaneous recuperation of the endocochlear ionic environment. 29,6062…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, after trauma has occurred, there is often inflammation and influx of macrophages to the injured region. Several studies have demonstrated that the spiral ligament contains bone marrow-derived cells that can differentiate into macrophages (89). Macrophages are known to promote regeneration after injury (90).…”
Section: Recovery Of the Spiral Ligament After Traumamentioning
confidence: 99%